2019
DOI: 10.1103/physrevmaterials.3.124414
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic, and magnetic properties of bulk and epitaxial LaCoO3 through diffusion Monte Carlo

Abstract: Magnetism in lanthanum cobaltite (LCO, LaCoO3) appears to be strongly dependent on strain, defects, and nanostructuring. LCO on strontium titanate (STO, SrTiO3) is a ferromagnet with an interesting strain relaxation mechanism that yields a lattice modulation. However, the driving force of the ferromagnetism is still controversial. Experiments debate between a vacancy-driven or straindriven mechanism for epitaxial LCO's ferromagnetism. We found that a weak lateral modulation of the superstructure is sufficient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 153 publications
(280 reference statements)
1
17
1
1
Order By: Relevance
“…As previously mentioned, we used the geometry obtained with SCAN (FM and U = 0) for the subsequent DMC calculations because the calculated lattice constant (for the 2 × 2 × 1 supercell) of 5.696 Å is identical with the experimental value of 5.69(1) Å. DMC has the zero-variance property which means that as the trial wave function approaches the exact ground state (i.e., the exact nodal surface), the statistical fluctuations in the energy reduce to zero . There have been instances where various sophisticated, oftentimes expensive methods have been used to optimize the nodal surface of the trial wave function. However, similar to other DMC studies of correlated magnetic materials, ,,,, we used a PBE+ U approach where the Hubbard U value was used as a variational parameter to optimize the nodal surface by using DMC (for the FM and AFM states of 2D MnO 2 ). The fact that we can determine the optimal U parameter variationally by using DMC makes our DMC results more reliable than DFT+ U , where in DFT+ U the U parameter is usually arbitrarily chosen or fitted to experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, we used the geometry obtained with SCAN (FM and U = 0) for the subsequent DMC calculations because the calculated lattice constant (for the 2 × 2 × 1 supercell) of 5.696 Å is identical with the experimental value of 5.69(1) Å. DMC has the zero-variance property which means that as the trial wave function approaches the exact ground state (i.e., the exact nodal surface), the statistical fluctuations in the energy reduce to zero . There have been instances where various sophisticated, oftentimes expensive methods have been used to optimize the nodal surface of the trial wave function. However, similar to other DMC studies of correlated magnetic materials, ,,,, we used a PBE+ U approach where the Hubbard U value was used as a variational parameter to optimize the nodal surface by using DMC (for the FM and AFM states of 2D MnO 2 ). The fact that we can determine the optimal U parameter variationally by using DMC makes our DMC results more reliable than DFT+ U , where in DFT+ U the U parameter is usually arbitrarily chosen or fitted to experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…19 There have been instances where various sophisticated, oftentimes expensive methods have been used to optimize the nodal surface of the trial wave function. 68−71 However, similar to other DMC studies of correlated magnetic materials, 23,31,33,43,72 we used a PBE+U approach where the Hubbard U value was used as a variational parameter to optimize the nodal surface by using DMC (for the FM and AFM states of 2D MnO 2 ). The fact that we can determine the optimal U parameter variationally by using DMC makes our DMC results more reliable than DFT +U, where in DFT+U the U parameter is usually arbitrarily chosen or fitted to experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, diffusion Monte Carlo calculations showed that the magnetic ground state of the LCO thin film highly depends on the La–La distance, with the rocksalt‐type HS/LS‐FM order becoming the most stable state at a specific compressive strain. [ 59 ] In terms of the exchange mechanism, this order mainly results from correlation superexchange, which refers to the magnetic interaction whereby two electrons of O 2− mediate the exchange coupling between neighboring HS and LS Co 3+ . More specifically, the double occurrence of AFM superexchange coupling along the HS Co 3+ d x2−y2 – O 2− p σ – LS Co 3+ d x 2 −y2 – O 2− p σ – HS Co 3+ d x2−y2 pathway could facilitate the FM ordering (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As there exists as of yet no reported values for an optimal value of U, U opt , we first estimated U opt . We used a procedure established in previous works 24,[43][44][45][46] that has proven to be a reliable and un-biased way to estimate U opt for transition-metal oxides. In this procedure, we minimize the DMC total energy of the PBE+U trial wavefunction as a function of U.…”
Section: A 2h-agniomentioning
confidence: 99%